Functional analysis of differently expressed ferroptosis-related genes in patients with mitral valve prolapse - Xie, Hui; Wang, Liushun; Tang, Yihu; Zhao, Meng; Wang, Zihao; Liu, Mingzhu; Zhao, Quangong; Zhou, Jingxin; Wu, Yanhu (Frontiers in Genetics, 2022)
Background The prevalence of mitral valve prolapse (MVP) in heart valvular diseases is globally increasing. However, the understanding of its etiology and pathogenesis is limited. So far, the relationship between ferroptosis-related genes and long non-coding RNAs (lncRNAs) in MVP remains unexplored. This study investigates the potential pathogenesis of ferroptosis-related genes in MVP and provides a therapeutic target for the disease. Methods Blood samples from patients with MVP and healthy volunteers were collected for transcriptomic sequencing to analyze the expression of ferroptosis-related differentially expressed genes (DEGs) and differentially expressed long non-coding RNAs (DElncRNAs Co-expression network of ferroptosis-related DEGs and DElncRNAs. Furthermore, this work conducted GO and KEGG enrichment analyses. Results CDKN2A, SLC1A4, ATF3, and other core genes related to the mitral valve prolapse were screened out. CDKN2A, SLC1A4, and ATF3 genes were at the core position of the network, regulated by numerous lncRNAs. Notably, these genes are primarily involved in the extracellular region and p53 signaling pathway. Conclusion In summary, CDKN2A, SLC1A4, and ATF3 regulate the pathophysiological process of MVP and are potential therapeutic targets.